Cricotracheostomy for patients with severe COVID-19: A case control study - Mukai, Naoki; Okada, Masahiro; Konishi, Saki; Okita, Mitsuo; Ogawa, Siro; Nishikawa, Kosuke; Annen, Suguru; Ohshita, Muneaki; Matsumoto, Hironori; Murata, Satoru; Harima, Yutaka; Kikuchi, Satoshi; et al. (Frontiers in Surgery, 2023)
Background: Tracheostomy is an important procedure for the treatment of severe coronavirus disease-2019 (COVID-19). Older age and obesity have been reported to be associated with the risk of severe COVID-19 and prolonged intubation, and anticoagulants are often administered in patients with severe COVID-19; these factors are also related to a higher risk of tracheostomy. Cricotracheostomy, a modified procedure for opening the airway through intentional partial cricoid cartilage resection, was recently reported to be useful in cases with low-lying larynx, obesity, stiff neck, and bleeding tendency. Here, we investigated the usefulness and safety of cricotracheostomy for severe COVID-19 patients. Materials and methods: Fifteen patients with severe COVID-19 who underwent cricotracheostomy between January 2021 and April 2022 with a follow-up period of ≥ 14 days were included in this study. Forty patients with respiratory failure not related to COVID-19 who underwent traditional tracheostomy between January 2015 and April 2022 comprised the control group. Data were collected from medical records and comprised age, sex, body mass index, interval from intubation to tracheostomy, use of anticoagulants, complications of tracheostomy, and decannulation. Results: Age, sex, and days from intubation to tracheostomy were not significantly different between the COVID-19/cricotracheostomy and control/traditional tracheostomy groups. Body mass index was significantly higher in the COVID-19 group than that in the control group (P = 0.02). The rate of use of anticoagulants was significantly higher in the COVID-19 group compared with the control group (P < 0.01). Peri-operative bleeding, subcutaneous emphysema, and stomal infection rates were not different between the groups, while stomal granulation was significantly less in the COVID-19 group (P = 0.04). Conclusions: These results suggest that cricotracheostomy is a safe procedure in patients with severe COVID-19.